Orthopedic Surgery Causes Gut Microbiome Dysbiosis and Intestinal Barrier Dysfunction in Prodromal Alzheimer Disease Patients: A Prospective Observational Cohort Study. Issue 2 (29th August 2022) - Liu, Fangyan; Duan, Mei; Fu, Huiqun; Zhao, Guoguang; Han, Ying; Lan, Fei; Ahmed, Zara; Cao, Guanglei; Li, Zheng; Ma, Daqing; Wang, Tianlong
Abstract : Objective: To investigate gut microbiota and intestinal barrier function changes after orthopedic surgery in elderly patients with either normal cognition (NC) or a prodromal Alzheimer disease phenotype (pAD) comprising either subjective cognitive decline (SCD) or amnestic mild cognitive impairment (aMCI). Background: Homeostatic disturbances induced by surgical trauma and/or stress can potentially alter the gut microbiota and intestinal barrier function in elderly patients before and after orthopedic surgery. Methods: In this prospective cohort study, 135 patients were subject to preoperative neuropsychological assessment and then classified into: NC (n=40), SCD (n=58), or aMCI (n=37). Their gut microbiota, bacterial endotoxin (lipopolysaccharide), tight junction (TJ) protein, and inflammatory cytokines in blood were measured before surgery and on postsurgical day 1, 3, and 7 (or before discharge). Results: The short-chain fatty acid (SCFA)-producing bacteria were lower while the gram-negative bacteria, lipopolysaccharide and TJ were higher preoperatively in both the SCD and aMCI (pAD) groups compared with the NC group. After surgery, a decrease in SCFA-producing bacteria, and an increase in both gram-negative bacteria and plasma claudin were significant in the pAD groups relative to the NC group. SCFA-producing bacteria were negatively correlated with TJ and cytokines in pAD patients on postsurgical day 7. Furthermore, surgery-induced perioperative metabolic stress and inflammatory responses were associated with gut microbiota alterations. Conclusions: Surgery exacerbates both preexisting microbiota dysbiosis and intestinal barrier dysfunction in pAD patients, all of which may be associated with systemic inflammation and, in turn, may lead to further cognitive deterioration.